How can we simplify sqrt(48) - 6/sqrt(3) ?

Observing that 48 = 24 * 2 = 1222 = 443, we can write square root of 48 as being square root of 443, which means that sqrt(48) = 22sqrt(3).Now, we can multiply the new result 22sqrt(3) with sqrt(3) such that we can have a common denominator on the bottom.So, 22sqrt(3)sqrt(3)/sqrt(3) - 6/sqrt(3) = (22*3 - 6)/sqrt(3) = 6/sqrt(3).If we want our answer to look prettier, we can multiply again with sqrt(3) such that the new result could look as 6 * sqrt(3) /3 = 2sqrt(3).

Answered by Dorian G. Maths tutor

8104 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find D when 8x^3-12x^2-2x+D is divided by 2x+1 when the remainder is -2


Differentiate y = 4exp(6x) + cos(x) + 6x


Find the area under the curve with equation y = 5x - 2x^2 - 2, bounded by the x-axis and the points at which the curve reach the x-axis.


Prove that the indefinite integral of I = int(exp(x).cos(x))dx is (1/2)exp(x).sin(x) + (1/2)exp(x).cos(x) + C


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences